Turnover and Distribution of 131Iodine-Labelled Human Fibrinogen - Amris, Annemarie; Amris, C. J (Thrombosis and Haemostasis, 1964)
14 patients (5 diabetics with arteriosclerotic complications, 4 patients with thrombo-embolic disease, 4 with cirrhosis, coagulation defects and increased fibrinolytic activity, and 1 cancer patient) and 3 control patients were subjected to turnover studies with 13iodine labelled human fibrinogen.Half-life times in the control patients were found to be 4 days, the fractional turnover rates 19–23 per cent, of intravascular fibrinogen per day, and the absolute turnover 0.02 to 0.06 gm per day per kg. body weight. The other patient’s half-life times and turnover rates varied considerably from 0.9–5.5 days, 13–160 per cent, per day of intravascular fibrinogen and 0.02–0.4 gm per day per kg. body weight respectively.As fibrinogen unlike other proteins subjected to turnover studies, is converted to fibrin, it is not possible to measure the true intra-extravascular distribution ratio of fibrinogen. But intravascular fibrinogen could be approximated to constitute 68–99 per cent, of the total fibrinogen. There is justification in believing that fibrinogen is degradated through a continuous coagulation in equilibrium with fibrinolysis, and that the organism contains a greater mass of fibrin, the “fibrin pool”. Considerations of the turnover mechanism can however only be hypothetical.